The attitude of the fishermen to fisheries extension officers Personnel (the case of fisherman in sejangat village, sub-district of bukit batu, bengkalis district, riau Province) - Yuyun Soraya; Kusai '; Eni Yulinda (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research was carried out in May 2014. It aims to know the characteristics of the fisherman,the attitude of the fishermen to fisheries extension officers personnel, and to measure the relationshipbetween the characteristics of the fishermen with the attitude of the fishermen to fisheries extensionofficers personnel in Sejangat Village, Sub-district of Bukit Batu, Bengkalis District, Riau Province.The respondents in this research was 48 people. Methods of analysis used is the attitude measurementtechniques “Likert scale” and Rank Spearman correlation analysis.The attitude of the fishermen to fisheries extension officers based on overall cognitivecomponent had a total score of 1532 in the category quite well with the range of scores (1248-1871).Onthe affective component as a whole had a score of 1780 is a category is good enough (1248-1871) andcomponent behavior had a total score of 960 in the categories less well (528-1055). Relationshipcharacteristics of fishing based on age, education, experience, number of dependents, and income withthe attitude of the fishermen had no significant or have no real correlation with the value P > α(0,05).Keywords: Attitude Of The Fishermen, Attitude Components, Fisheries Extension Officers, SejangatVillag